Metrological support of the manufacture of flame detectors - Докторович, Ірина Василівна; Годованюк, Василь Миколайович; Юр’єв, Василь Григорович (Eastern-European Journal of Enterprise Technologies, 2014)
When developing any product, measures on ensuring the metrological support of its manufacture are taken. First of all, the search and selection of measurement tools of basic parameters, selection of control devices and methods of parameters measurement, study of their metrological characteristics is carried out. Especially when it comes to products that must work in threshold mode and respond to small changes in operating conditions. These devices are flame detectors. Radiation spectrum, which lies in the near infrared region is the most informative for detectors. Radiometers are used for the IR radiation parameters control. IR radiometer was developed for the metrological support of the manufacture of flame detectors. The results of investigating the metrological characteristics of IR radiometer are given in the paper. Since the primary transducer (photodetector) is sensitive in a wide spectral range, any extraneous optical radiation is background. To reduce its impact, the radiometer sensitivity was limited to the range of 4-5 microns, which is different from the control photodetector sensitivity range. Therefore, the metrological characteristics of measurement procedures were determined as well. As a result of the studies, high sensitivity in a wide range of irradiance variation - from 0.001 to 20 W/m2 was confirmed. Conditions of measurement with a relative irradiance measurement error that is within ± 6% was revealed.